Analisis Tingginya Penjualan Album KPop Dalam Pertumbuhan Ekonomi di Indonesia - Yuliawan, Rahmat; Sudarnice, Asia; Windaputri, Nessa; Aurelly, Kyra Prudence (Pustaka Galeri Mandiri, 2023)
This study aims to determine the high sales of K-pop albums on economic growth, identify factors that contribute to high sales of K-pop albums, understand how the popularity of K-pop in Indonesia affects consumer spending patterns, explain the role of social media and online platforms in promoting K-pop album sales in Indonesia. The study uses a mixed method by combining quantitative and qualitative approaches. Quantitative data were obtained from official sources such as the Central Bureau of Statistics and reports on K-pop album sales in Indonesia. While qualitative data were collected through in-depth interviews with stakeholders in the music industry, such as distributors, music stores, and K-pop fans. The results of the study found several interesting things including The Courtship, The Relationship, The Marriage, Kpop Album Marketing Strategy Through Online Media and the Influence of Album Quality on the Interest in Buying Physical Kpop Music Albums Quality.